Potentially Serious Drug Interactions Resulting From the Pretravel Health Encounter. (22nd October 2018) - Sbaih, Nadine; Buss, Brian; Goyal, Dheeraj; Rao, Sowmya R; Benefield, Russell; Walker, Allison Taylor; Esposito, Douglas H; Ryan, Edward T; LaRocque, Regina C; Leung, Daniel T; ,
Abstract: Travelers seen for pretravel health encounters are frequently prescribed new travel-related medications, which may interact with their previously prescribed medications. In a cohort of 76 324 travelers seen at 23 US clinics, we found that 2650 (3.5%) travelers were prescribed travel-related medications with potential for serious drug interactions.